A comparative study of biomass and carbon pool between natural and degraded mangrove forests in Peninsular Malaysia / Zhila Hemati - Zhila Hemati, - (2015)

(untitled)
The present study involves the assessment of biomass concentration and carbon pool potentials of two major mangrove forests in Peninsular Malaysia; natural mangrove (Kuala Selangor) and degraded mangrove (Sg. Haji Dorani) forests. Various approaches adopted on the study ranged from biodiversity assessment, biomass estimation, to physico-chemical characterizations and estimation of carbon pool potentials. Components of the mangrove assessed included litter production: leaves, stem, branch, propagules and roots across three (3) seasons of Peninsular Malaysia. Shannon- Weniner index (H') was used to assess the species diversity indices while Simpson's index (Ds) and Sorenson‟s Similarity index (S) were used to estimate the species richness indices of both mangrove areas. Statistical tools (SPSS & Ms Excel) were used to validate and analyze generated data. The forest trees distribution with the study areas gave a population count of 703 individual trees; 302 individuals for KSNP and 401 for SHD. Further investigation among the trees population revealed that species diversity was higher in SHD (5 species) than those found in KSNP (4 species). Avicennia marina, Bruguiera cylindrica, Excoecaria agallocha, Xylocarpus mekongensis characterized SHD, and Avicennia officinalis, Bruguiera parviflora, Rhizophora mucronata characterized KSNP, yet a tree species was common to both areas; Sonneratia alba. Both areas had a total above- ground biomass of 428.24 t ha-1 yr- 1; 305.46 t ha-1 yr-1 from KSNP and 122.78 t ha-1 yr-1 from SHD. The most pronounced above-ground biomass species were B. parviflora (266.74 t ha-1 yr -1) II for KSNP and A. marina (108.63 t ha-1yr -1 for SHD). Hence, when both species were further assessed, it was found that the highest percentage of above-ground biomass in tree components was recorded from the stem; 61.62 t ha-1 yr-1for B. parviflora and 49.66 t ha-1 yr-1 for A. marina. In general, the rate of litter production individually ranged from 0.08 to 6.59 g m2 day and 0.09 to 8.82 g m2 day for SHD and KSNP, respectively. The maximum individual rate was found in propagules litter where 8.82 g m2 day was recorded in KSNP and 4.36 g m2 day found in SHD. Such development might depict an enriched nature of KSNP as an undisturbed mangrove forest. The carbon concentration in KSNP was pronounced in the stem of B. parviflora (31.87 t C ha-1 yr-1) and A. officinalis (14.31 t C ha-1 yr-1), and it directly influenced the corresponding carbon sequestration potential of the plant parts where 126.37 t C ha-1 yr -1 and 54.46 t C ha-1 yr -1 were found in B. parviflora and A. officinalis, respectively. Though the stem contained highest carbon concentration in SHD as well, yet it did not directly influence corresponding carbon sequestration potential trend as in the case of KSNP. The total carbon sequestration potential of the living plant parts of KSNP was 125.83 t C ha-1 yr -1while SHD recorded 97.15 t C ha-1 yr -1. Such variation in the organic carbon content, carbon concentrations and carbon sequestration potentials of different parts of the mangrove species can be due to biological activities of plants. Finally, the net primary productivity showed that KSNP (14.92 t ha-1 yr -1) than SHD (13.87 t ha-1 yr -1) despite the higher species diversity found in SHD. This may be due to species types and some other associated environmental factors.